Currency movements within and outside a currency union: The case of Germany and the euro area - Franz Seitz; Gerhard Rösl; Nikolaus Bartzsch (Hochschule für angewandte Wissenschaften Amberg-Weiden (HAW), 2011)
In this paper, we analyze the volume of euro banknotes issued by Germany within the euro area with several seasonal methods. We draw a distinction between movements within Germany, circulation outside Germany but within the euro area and demand from non-euroarea countries. Our approach suggests that only about 20% of euro notes issued by Germany are used for transactions in Germany. The rest is hoarded (10%), circulates in other euro area countries (25%) or is held outside the euro area (45%). – – In dem vorliegenden Papier analysieren wir die Emissionen von Euro-Banknoten durch die Deutsche Bundesbank anhand verschiedener saisonaler Ansätze. Wir unterscheiden zwischen der Nachfrage aus Deutschland, der Haltung in anderen Euro-Ländern und Umlauf außerhalb des Euro-Währungsgebiets. Es stellt sich heraus, dass nur ca. 20 % der emittierten Banknoten für Transaktionszwecke in Deutschland gebraucht werden. Der Rest wird aus unterschiedlichen Gründen gehortet (10 %), läuft in anderen EWU-Ländern um (25 %) oder wird außerhalb des Euro-Raums gehalten.
Keywords: E41; E42; E58; 330; Banknotes; euro; foreign demand; hoarding; transaction balances